1973
DOI: 10.1139/m73-069
|View full text |Cite
|
Sign up to set email alerts
|

Glucose flux at the sediment–water interface of Toronto Harbour, Lake Ontario, with reference to pollution stress

Abstract: Cycling of glucose at the sediment–water interface was determined through coupling measurement of natural substrate concentrations with heterotrophic uptake by the natural microbial communities in the sediment and in the water column. The same general pattern was found for both polluted and less polluted parts of Toronto Harbour, so that other labile organic species possibly have similar cycles. Velocity of uptake of glucose (flux) and turnover time showed no relationship to either substrate concentration or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The turnover times reported here are generally qua1 to or longer than those reported for aerobic uptake in lake or subtidal sediment slurries (Wood 1970;Hall ct al. 1972;IIarrison et al 1971;Wood and Chua 1973).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The turnover times reported here are generally qua1 to or longer than those reported for aerobic uptake in lake or subtidal sediment slurries (Wood 1970;Hall ct al. 1972;IIarrison et al 1971;Wood and Chua 1973).…”
Section: Discussionmentioning
confidence: 44%
“…1972;IIarrison et al 1971;Wood and Chua 1973). In most studies samples were taken from the upper centimeter, although Wood (1970) did examine activity with depth and found longer turnover times with increasing depth. In a study of anaerobic lactate utilization, a turnover time of less than 30 min was reported for lake sediments (Cappenberg and Prins 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Because the water temperature in this part of the Arctic Ocean varies by only 2-3 C" seasonally, it was postulated that nutrients may cause the change. Carney and Colwell (1976) and Wood and Chua (1973) established a positive correlation between percentage respiration and pollution levels in Baltimore Harbor and Toronto Harbor respectively. The observations may, however, have been more strictly applicable to levels of eutrophication in these harbours as Goulder e t al.…”
Section: Resultsmentioning
confidence: 97%
“…Heterotrophic activity Uptake expressed as pg glucose I-' h-'. Percent respiration calculated as respired uptake divided by total uptake ( a ) JH-glucose uptake (After Azam and Holm-Hansen, 1973) Cruise River Plume Strait T V,,, , , T=Turnover time in hours V,,,, expressed in pg glucose 1-' h-' K t + Sn expressed in pg glucose 1-' Hobbie and Crawford (1969b) Pamlico River Estuary "C 3.25-9.5 Crawford et al (1974) Pamlico River Estuary I4C 0.15-24.1 0.2-22 0.83-49.9 Vaccaro and Jannasch (1966) Woods Hole Dock 1 4~ 0.275 1.6 Seki et al (1969) Nanaimo River Estuary I4C' 0.187-156 Wood and Chua (1973) Toronto Harbour "C 0.51-10.59 12-304 20-37 1 Seki et al (1975) Tokyo Bay 14C 18 8.7 155…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of this discussion, the term "sediment-water interface" will indicate the top layer of sediment (<1 mm) as sampled in this and a previous study (13). Unfortunately, others (18) have used the terms sediment and sediment-water interface interchangeably. As shown in a previous study (13), the interface is quite distinct from the sediment immediately below.…”
Section: Methodsmentioning
confidence: 99%